Testing the validity of free cash flow hypothesis: Evidence from Nigeria - Nnenna Georgina Nwonye; Sebastine Ugochukwu Ugwuegbe (International Journal of Financial, Accounting, and Management, 2019)
Purpose: This study empirically tests the validity of the free cash flow hypothesis among firms quoted on the Nigerian Stock Exchange (NSE) from 2007 to 2017. Research methodology: The study employed a dynamic panel system Generalized Method of Moments (GMM) in analyzing the data generated. Results: the result failed to provide empirical evidence in support of the Jensen free cash flow hypothesis in Nigeria. The equally showed that a high concentration of shareholding in the hand of a few individual increases the amount of dividend paid out to shareholders. The result is however robust using different methods. Limitations: We focused only on testing the validity of the free cash flow hypothesis proposed by Jensen (1986). Contribution: The study provided empirical evidence that invalidates the propositions of the free cash flow hypothesis among publicly quoted firms in Nigeria. The result is robust using different estimation techniques. Keywords: Free cash flow hypothesis; Dividend payout